A Split-Decoding Message Passing Algorithm for Low Density Parity Check Decoders - Mohsenin, Tinoosh; Baas, Bevan M. (Journal of signal processing systems, 2010)
A Split decoding algorithm is proposed which divides each row of the parity check matrix into two or multiple nearly-independent simplified partitions. The proposed method significantly reduces the wire interconnect and decoder complexity and therefore results in fast, small, and high energy efficiency circuits. Three full-parallel decoder chips for a (2,048, 1,723) LDPC code compliant with the 10GBASE-T standard using MinSum normalized, MinSum Split-2, and MinSum Split-4 methods are designed in 65 nm, seven metal layer CMOS. The Split-4 decoder occupies 6.1 mm 2 , operates at 146 MHz, delivers 19.9 Gbps throughput, with 15 decoding iterations. At 0.79 V, it operates at 47 MHz, delivers 6.4 Gbps and dissipates 226 mW. Compared to MinSum normalized, the Split-4 decoder chip is 3.3 times smaller, has a clock rate and throughput 2.5 times higher, is 2.5 times more energy efficient, and has an error performance degradation of 0.55 dB with 15 iterations.